Between-limb differences in running technique induces asymmetric negative joint work during running - Hashizume, S.; Hobara, H.; Kobayashi, Y. (European Journal of Sport Science, 2019)
Negative work, which is mainly generated by eccentric muscle contraction, has an important influence on the associated muscle damage. Generally, mechanical parameters are determined for one side of a lower extremity on the assumption of negligible between-limb differences. However, between-limb differences in the negative work of lower extremity joints during running remain unclear. This study examines between-limb differences in negative work and associated mechanical parameters during the contact phase of running. Twenty-five young adult males voluntarily participated in this study. Each participant was asked to run on a straight runway at a speed of 3.0 m s-1. Negative work, amplitude, duration of negative power, moment, and angular velocity were computed for both sides of the lower extremities. Significant differences were found in negative work between limbs for the hip (18.9 ± 11.7%), knee (13.6 ± 10.4%), and ankle (11.8 ± 8.5%) joints. For the hip joint, asymmetric negative work was attributable to the between-limb difference in the amplitude of negative power owing to a corresponding difference in the moment. The between-limb differences concerning the duration and amplitude of negative power could explain the asymmetric negative work in the knee joint. The asymmetric negative work of the ankle joint was attributable to the between-limb difference in the amplitude and duration of the negative power and the moment. These results indicate that asymmetric negative work was generated in each lower extremity joint; however, the major mechanical parameters corresponding to the negative work are not the same across the joints.